2016
DOI: 10.1016/j.bjorl.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Audiological profile of patients treated for childhood cancer

Abstract: The auditory feature found after the cancer treatment was a symmetrical bilateral sensorineural hearing loss. Chemotherapy with cisplatin proved to be a risk factor, while head and neck radiotherapy was not critical for the occurrence of hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 33 publications
(39 reference statements)
1
25
0
Order By: Relevance
“…One of the studies analyzed in this review observed that 26% of the individuals presented high-frequency sensorineural hearing loss, whose appearance began from one to 60 months after the end of the chemotherapy, regardless of individual or cumulative doses of cisplatin 20 . Another three studies also verified percentages of alterations ranging from 24 to 100%, from 6 to 44 months after, the main hearing loss being the sensorineural, bilateral and symmetric 22,23,[25][26][27] .…”
Section: Results Of the Audiological Assessment And Occurrence Of Otomentioning
confidence: 81%
See 4 more Smart Citations
“…One of the studies analyzed in this review observed that 26% of the individuals presented high-frequency sensorineural hearing loss, whose appearance began from one to 60 months after the end of the chemotherapy, regardless of individual or cumulative doses of cisplatin 20 . Another three studies also verified percentages of alterations ranging from 24 to 100%, from 6 to 44 months after, the main hearing loss being the sensorineural, bilateral and symmetric 22,23,[25][26][27] .…”
Section: Results Of the Audiological Assessment And Occurrence Of Otomentioning
confidence: 81%
“…Considering that the aim of this research was to verify the effects of cisplatin and carboplatin chemotherapy on the auditory system of children and/or adolescents with cancer, the selected studies tended to be longitudinal, assessing the individuals before, during and/or after chemotherapy; the follow-up after chemotherapy ranged from one month to 127 months. Only five studies performed the assessment exclusively post-chemotherapy treatment 4,22,27,29,36 .…”
Section: Methodological Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations